Metal destruction in process of manufacturing parts from molybdenum and niobium - Rasulov, Z.N.; Usanov, D.N.; Voinash, S.A.; Malikov, V.N.; Karnaukhov, A.I.; Ishkov, A.V.; Fadeev, D.A. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The effect of coatings with surface-active properties and aerothermoacoustic treatment on Mo and Nb stampability, mechanical properties, and microdistortions of the crystal lattice is considered. An improvement in the quality of products obtained by drawing using these technologies has been established due to an increase in plasticity and a decrease in microdistortions of the crystal lattice. Modification of the surface of the tool reduces distortion in the micro-regions of the crystal lattice, reducing the stresses of the 2nd and 3rd kind of deformed Nb and improving its formability and the quality of semi-finished products and finished products. Low formability of Mo and Nb is associated with the presence of brittle phases of lamellar and sharp-edged shape, which reduce ductility and toughness. For Nb, an additional negative factor is the presence of grains up to 40–50 μm in size.
Keywords: coatings; molybdenum; niobium; microstructure; aero thermoacoustic treatment; deformability